A novel case of ocular cicatricial pemphigoid induced by levamisole-adulterated cocaine. Issue 1 (April 2021) - Igwe, Chinedu N; Robinson, Fiona; Jones, Sophie M
Aim: To report a case of ocular cicatricial pemphigoid caused by levamisole-adulterated cocaine. Methods: Case report. Results: A 54-year-old woman with multi-systemic levamisole-induced vasculitis which triggered bilateral cicatrizing conjunctivitis refractory to conventional immunosuppressants due to continued cocaine misuse. Conclusion: Levamisole-induced vasculitis is a significant public health issue due to its popularity as an adulterant to cocaine. Our report suggests that levamisole caused vasculitis and ocular cicatricial pemphigoid in this case. Ocular manifestation of this syndrome is rare.